تقييم مدى استجابة المؤسسة الاقتصادية لمفهوم المسؤولية الاجتماعية دراسة حالة مؤسسة المطاحن الكبرى في جنوب بسكرة - بن خليفة, حمزة; روينة, مخلخل (جامعة الوادي - University of Eloued, 2019)
نحاول في هذه الدراسة اختبار مدى تبني المؤسسة الاقتصادية لمفهوم المسؤولية الاجتماعية بأبعادها الأربعة (مسؤوليتها الاقتصادية، مسؤوليتها الأخلاقية، مسؤوليتها القانونية ومسؤوليتها الإنسانية)، حيث تم إجراء الدراسة التطبيقية على مؤسسة المطاحن الكبرى للجنوب بسكرة بحيث تم جمع البيانات الأولية بصورة رئيسية اعتماداً على 38 استبيانا بحثيا فيما تمثلت المعلومات الثانوية في المقالات والدراسات السابقة للموضوع. أظهرت نتائج الدراسة أن مؤسسة المطاحن الكبرى للجنوب تحاول تطبيق مفهوم المسؤولية الاجتماعية بأبعادها الأربعة ،البعد الاقتصادي، القانوني، الأخلاقي، الإنساني The objective of this study is to clarify the role of environmental levies in achieving sustainable development, By recognizing the environment and Environmental Collection, and to address the importance of sustainable development and its dimensions, in addition to the contribution of the Algerian environmental tax structure to achieving sustainable development. One of the most important results is the need to urge economic institutions to cooperate with environmental associations, In addition to the inefficient environmental tax system which led to the inability to direct enterprises to reduce pollution
Assessing the economic institution's response to the concept of social responsibility, the case study of the Great Mills Corporation in South Biskra
مقال
Keywords: المسؤولية الاجتماعية ،البعد الاقتصادي ،البعد القانوني ،البعد الأخلاقي ،البعد الإنساني; The environment, Environmental Collection, Environmental tax, Sustainable development.